PELAKSANAAN PERMENDIKBUD NO. 65 TAHUN 2013 TENTANG STANDAR PROSES (Pendekatan Saintifik) PADA KEGIATAN INTI DALAM PEMBELAJARAN SOSIOLOGI DI KELAS X IPS SMA NEGERI 4 PADANG - Aknimal, Migo Wahyu (Pendidikan Sosiologi, 2014)
The research is the background by the government policy on the development ofcuuriculum, that replacement KTSP curriculum to the Curriculum 2013 which established in2013 ago. The curriculum KTSP in the learning process, activities consist of the exploration,elaboration, and confirmation. While the curriculum 2013, the activities of learning processknown as the scientific approach consist of learning of observing, question, reason, andcommunicate. To reach the process there are stage of affective, cognitive, and skill. The studito described the activities of the teacher in conducting a scientific approach to teaching insociology learning in first class social science senior hight school 4 Padang city.The teory used is a social fact by Emile Durkheim. The study used a qualitativeapproach the type of evaluative research. Informant in the study are representative ofcurriculum, sociology teacher and student in first class social science senior hight school 4Padang City. Informants selection in this study purposive sampling. The type of data used isprimary data and secondary data. Method of data collection is 1) observation, 2) interviewsin-depth, 3) documentation study. Data analysis was performed with a model of interaktifanalysis (Miles and Huberman) include four stage 1) data collection 2) data reduction, 3)presentation of data, 4) conclution.The result of the study based data obtained concluded, 1) one of the teacher in firstclass social science studies sociology Senior Hight School 4 Padang city, does not understandthe scientific approach. That is in the process of affective. 2) the teacher of the first classsocial science sociology studies in Senior Higth School 4 Padang city, a learning resourchusing still that is textbook, teacher prefer to wait from the school to get learning learningresourch related. 3) the teacher of first class social science sociology studies in the hightschool 4 Padang city, inaffective and inconsistent providing opportunities to student inconducting scientific approach in the learning process.